2004
DOI: 10.1088/0268-1242/19/10/004
|View full text |Cite
|
Sign up to set email alerts
|

The electron effective mass at the bottom of the GaNAs conduction band

Abstract: We determined the electron effective mass, m * e , from the photoluminescence (PL) of GaN x As 1−x /GaAs single quantum wells. The energy of the interband optical transitions is analysed within the frame of the band anti-crossing model (BAC), which accounts for a highly nonparabolic nature of the GaNAs conduction band (CB). From the PL we found that m * e at the bottom of the CB in GaN x As 1−x /GaAs quantum wells (QWs) increases from 0.095m 0 to 0.12m 0 for x increasing from 0.009 to 0.04. We found that the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Earlier studies have shown that the electron mobility of ͑In͒GaAs 1−x N x decreases significantly with N composition, x, [1][2][3][4][5][6] presumed to be partly due to the influence of N incorporation on the effective mass, m ‫ء‬ . 3,4,7,8 There have been conflicting experimental 3,7-9 and theoretical 8,10,11 reports on the x and temperature, T, dependences of m ‫ء‬ . For x Ͻ 0.005, m ‫ء‬ was reported to either decrease 4 or rapidly increase 3,7,9 with increasing x.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that the electron mobility of ͑In͒GaAs 1−x N x decreases significantly with N composition, x, [1][2][3][4][5][6] presumed to be partly due to the influence of N incorporation on the effective mass, m ‫ء‬ . 3,4,7,8 There have been conflicting experimental 3,7-9 and theoretical 8,10,11 reports on the x and temperature, T, dependences of m ‫ء‬ . For x Ͻ 0.005, m ‫ء‬ was reported to either decrease 4 or rapidly increase 3,7,9 with increasing x.…”
Section: Introductionmentioning
confidence: 99%
“…The electron effective mass in dilute-nitride QWs has been predicted by theories [28][29][30][31][32] and observed experimentally 25,[33][34][35][36][37] to be larger than those containing materials without nitrogen. In the case of GaNAs, there is an agreement that while the electron effective mass is increased with the presence of nitrogen, it was not as high as suggested by initial reports.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the two formed sub-bands are highly non-parabolic. However, limiting our focus around the critical point Γ, it is listed that the effective mass in the case of diluted nitrogen becomes much larger (about 2-fold) than in GaAs as the nitrogen is incorporated [63]. …”
Section: Methodsmentioning
confidence: 99%